Staggered enforcement of infection control and prevention measures following four consecutive potential laboratory exposures to imported Brucella melitensis - V.Y. Miendje Deyi; M. Mori; N. Dauby; P. Clevenbergh; B. Mahadeb; A. Loizidou; E. Maillart; D. Martiny; A.L. Debyttere; M. Gerard; M. Hallin (Elsevier, 2021)
Summary: From 2015 until 2020, Brucella melitensis was isolated four times in our microbiology laboratory. All patients had travelled in endemic-areas. Immediately after the first occurrence, all laboratory staff were risk-stratified and preventive and protective measures were applied according to CDC guidelines. Nineteen workers were exposed and needed chemoprophylaxis and follow-up. At each subsequent occurrence, risk analysis was performed, and additional measures were implemented accordingly, leading to a progressive reduction of exposed staff members to none the fourth time. We describe here the additional measures that permitted this important exposure reduction.